Tingkat Kerusakan Jalan Dengan Metode Pci Dan Bina Marga Pada Ruas Guluk-Guluk Ketawang Laok Sumenep - Ainun Syafi'an; Ahmad Suwandi (Jurnal Teknik Sipil, 2021)
Roads are crucial land transportation infrastructure for the growth and seamless operation of commercial, social, and cultural activities. One of the connecting routes between Guluk-Guluk District and Ganding Regency to the Regency is Jalan Guluk-guluk Ketatang Laok (No.378) Guluk-guluk District, Sumenep Regency. The goal of this study is to establish the extent of road damage on the flexible pavement layer on the Guluk-guluk Tawang Laok (No.378) road section, as well as a strategy for restoring the 1 kilometer long road that has been damaged. Quantitative approaches are used to acquire data, which include on-site surveys and data from relevant agencies. This study employs two methods, the PCI and Binamarga methods, with the PCI method yielding recommendations for pavement reconstruction in segments 1 - 4, patching in segments 4 - 8, and routine maintenance in segments 8 - 10, while the Binamarga method yields recommendations for periodic maintenance in segments 1 - 4, patching in segments 4 - 8, and routine maintenance in segments 8 - 10.